2019
DOI: 10.1259/dmfr.20180331
|View full text |Cite
|
Sign up to set email alerts
|

Can a high-density dental material affect the automatic exposure compensation of digital radiographic images?

Abstract: Objectives: To investigate the influence of high-density dental material on the automatic exposure compensation of digital radiographic imaging systems. Methods: Two radiographic phantoms were custom made to reproduce radiographic densities of the dental tissues: enamel, dentin and pulp chamber. The phantoms were X-rayed using the Digora Toto, Digora Optime and VistaScan systems for 0.063, 0.1 and 0.16 s. Radiographic acquisitions were repeated in the presence of a high-density material equivalent to a titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
(16 reference statements)
0
17
3
Order By: Relevance
“…Similarly, in another in-vitro study, AEC altered the dental tissue-equivalent gray values in the presence of a material equivalent to a titanium implant. 6 Nevertheless, the present study revealed that the AEC-related gray value variation of the radiographic image was not sufficient to affect the diagnostic accuracy of proximal carious lesions, which may be attributed to the simulation of a clinical condition with much more attenuating structures. The radiographic detection of proximal caries has been studied extensively in the literature; 1,10,11,12,13 however, the objectives addressed have focused mostly on the comparison between analogue and digital systems, 1,10,12,13 and the use of post-processing methods.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Similarly, in another in-vitro study, AEC altered the dental tissue-equivalent gray values in the presence of a material equivalent to a titanium implant. 6 Nevertheless, the present study revealed that the AEC-related gray value variation of the radiographic image was not sufficient to affect the diagnostic accuracy of proximal carious lesions, which may be attributed to the simulation of a clinical condition with much more attenuating structures. The radiographic detection of proximal caries has been studied extensively in the literature; 1,10,11,12,13 however, the objectives addressed have focused mostly on the comparison between analogue and digital systems, 1,10,12,13 and the use of post-processing methods.…”
Section: Discussioncontrasting
confidence: 59%
“…In addition, we believe that the location and amount of high-density material in the radiograph did not influence our results, because the action of the AEC seems to be based mainly on the highest and lowest pixel values of the image, and not on the quantity and location of these pixels. 3,6 Furthermore, because this was an ex-vivo study, it had the relevant limitation of lacking clinical signs (sensitivity and/or pain) in the diagnostic process. Conversely, the present methodology enabled greater control of the variables, standardization of the radiographic acquisitions and comparison of the diagnosis with a reference standard, factors that contributed toward obtaining sounder results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that AEC can improve the accuracy of diagnosis of proximal caries in under- and overexposed images [ 4 ]. It was also stated previously that the effect of AEC is influenced by the presence of high-density objects [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 83%
“…In some systems, image enhancement is also performed automatically by the software, after image acquisition, but before it is displayed on the monitor, through an image pre-processing tool called Automatic Exposure Compensation (AEC) [ 4 6 ]. This tool increases image contrast, modifying pixel values non-linearly, producing high-contrast radiographs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%